Effect of Aspiration Therapy on Obesity-Related Comorbidities: Systematic Review and Meta-Analysis - Pichamol Jirapinyo; Diogo T. H. de Moura; Laura C. Horton; Christopher C. Thompson (Clinical Endoscopy, 2020)
Background/Aims Aspiration therapy (AT) involves endoscopic placement of a gastrostomy tube with an external device that allows patients to drain 30% of ingested calories after meals. Its efficacy for inducing weight loss has been shown. This study aimed to assess the effect of AT on obesity-related comorbidities. Methods A meta-analysis of studies that assessed AT outcomes was conducted through December 2018. Primary outcomes were changes in comorbidities at 1 year following AT. Secondary outcomes were the amount of weight loss at up to 4 years and pooled serious adverse events (SAEs). Results Five studies with 590 patients were included. At 1 year, there were improvements in metabolic conditions: mean difference (MD) in systolic blood pressure: -7.8 (-10.7 – -4.9) mm Hg; MD in diastolic blood pressure: -5.1 (-7.0 – 3.2) mm Hg; MD in triglycerides: -15.8 (-24.0 – -7.6) mg/dL; MD in high-density lipoprotein: 3.6 (0.7–6.6) mg/dL; MD in hemoglobin A1c (HbA1c): -1.3 (-1.8 – -0.8) %; MD in aspartate transaminase: -2.7 (-4.1 – -1.3) U/L; MD in alanine transaminase: -7.5 (-9.8 – -5.2) U/L. At 1 (n=218), 2 (n=125), 3 (n=46), and 4 (n=27) years, the patients experienced 17.8%, 18.3%, 19.1%, and 18.6% total weight loss (TWL), corresponding to 46.3%, 46.2%, 48.0%, and 48.7% excess weight loss (EWL) (p<0.0001 for all). Subgroup analysis of 2 randomized controlled trials (n=225) showed that AT patients lost more weight than did controls by 11.6 (6.5–16.7) %TWL and 25.6 (16.0–35.3) %EWL and experienced greater improvement in HbA1c and alanine transaminase by 1.3 (0.8–1.8) % and 9.0 (3.9–14.0) U/L. The pooled SAE rate was 4.1%. Conclusions Obesity-related comorbidities significantly improved at 1 year following AT. Additionally, a subgroup of patients who continued to use AT appeared to experience significant weight loss that persisted up to at least 4 years.